Molecular basis of the chikungunya virus replication complex assembly: platform for antiviral discovery - Tan, Yaw Bia (Nanyang Technological University, 2023)
RNA viruses like alphavirus, flavivirus, coronavirus, enterovirus, and picornavirus are one of the major infectious diseases worldwide. The current coronavirus 2019 (COVID-19) outbreaks imposed immense burden on global healthcare and economic. Chikungunya virus (CHIKV) from the alphavirus genus and Togaviridae family is another medically important positive-sense (+) single-stranded RNA (ssRNA) virus and a re-emerging mosquito-borne virus. CHIKV is often misdiagnosed as dengue and zika virus infections due to the same transmission vector (Aedes mosquitoes) and their similarity in clinical symptoms. CHIKV infections cause debilitating febrile illness accompanied by polyarthritis, myalgia, and rashes. Severe CHIKV infections may result in chronic rheumatoid-like joint-pain to years in the post-infection setting but is rarely lethal. Hence, CHIKV leads to increased healthcare and socioeconomic burden with rising outbreaks at an alarming rate due to multiple factors such as global warming, international travel, excessive urbanization, and increased transmission rate by novel CHIKV variants. CHIKV which was originally endemic in the West African zone has been spreading to the Asia, America, and Europe and resulted in the appearance of Western Africa, East-Central South African and the Asian genotypes. As a member of alphaviruses, CHIKV possesses a single partite +ssRNA genome of length ~11.8 kb, containing two reading frames for viral protein expression, a 5’ untranslated region (UTR) with methyl-guanosine cap, a 3’UTR with polyA tail, and an internal subgenomic promoter. Closely resembling a messenger RNA, the upstream reading frame of CHIKV genome encodes four nonstructural proteins (nsPs: nsP1-4) for viral RNA replication while the downstream reading frame encodes structural proteins (SPs) for virion packaging. The nsPs are autoprocessed to assemble into functional replication complexes (RCs) to perform viral RNA replication to sequentially produce the negative sense single-stranded RNA (-ssRNA), and +ssRNA which exist in double-stranded RNA intermediates. These viral replication process occurs within the CHIKV-induced membrane invagination, namely spherule, predominantly at the host plasma membrane (PM). The spherule compartment protects the viral RNA replication and minimizes the exposure to the host innate immune responses. The structures of the RC on the spherule were not determined to high resolution due to missing structural information on the alphaviral polymerase nsP4 and inter-nsPs interaction mapping. This work summarizes my success on the multiscale structural, biochemical, and biophysical characterizations for: (I) alphavirus nsP4 for its role in the viral RNA synthesis, (ii) interaction network between nsPs, (iii) in vitro reconstituted RC core comprising of recombinant nsP1, nsP2 and nsP4, (iv) the native CHIKV RC architecture on cellular level, and (v) replication dynamics of CHIKV. The high-resolution reconstituted RC core of 2.8 Å revealed a unit of viral polymerase nsP4, interacting with nsP2 helicase-protease, while sitting within the central pore of membrane-embedded nsP1 ring, known for capping activity. The RC core showed positive viral RNA polymerization activity. At the cellular level, an ultrastructure of CHIKV RC attached to the neck of spherule was discovered at ~7 Å with extra cytoplasmic density coordinated above the nsP1 C-terminus tail of the RC core. The CHIKV RC ultrastructure represents the holoenzyme state of RC (holo-RC) comprising of viral RNA, viral nsPs, and likely host factors. The CHIKV holo-RC shows conserved crown-like ring architecture shared by other RNA viruses like coronavirus and 12 nodavirus. This replication dynamics of the negative sense RNA synthesis was also captured in the bacterial replication assay developed. These results provide major advances on the molecular basis of the viral replication process of CHIKV as well as a broadly applicable platform for antiviral therapeutics development among alphaviruses and likely for other RNA viruses.